A Cross Sectional Study of Knowledge and attitudes levels about Polio Vaccination among selected sample of Technical Institute \ AL-Suwaira staff members - Jasim Mohammed Muhsin; Ahmed Kadhim Jawad (Diyala Journal of Medicine, 2019)
Background: The previous laboratory investigations confirmed local polio case was informed on 28th  January 2000 and another two wild polio cases were reported from Resafa \ Baghdad province in 2014. The date of onset of these cases were February and April 2014 and both cases were connected to 2013 of Syria outbreak.